(untitled) (International Journal of Business, Economics and Management, 2017)
The study investigates the effects of Corporate Social Responsibility on Banks Financial Performance in Nigeria with special reference to United Bank of Africa (UBA) Plc. The study utilized secondary sources of data, which were sourced from UBA’s annual report. The data sourced, spanned from 1992 – 2014. Data disaggregating into health issue, transportation and education proxies as Corporate Social Responsibility and Return on Equity as financial performance. The Ordinary Least Square (OLS) Estimation technique and Granger-causality test were adopted. The findings of the study suggests that there is insignificance relationship between Corporate Social Responsibility and financial performance. The paper recommends that management should see Corporate Social Responsibility as a business opportunity that is beneficial in the long run thereby, incorporating credible and well-structured social responsibility policies.